2003
DOI: 10.1021/ja034342r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Immunological Properties of Carbon Nanotubes Functionalized with Peptides

Abstract: Carbon nanotubes (NTs) are becoming highly attractive molecules for applications in medicinal chemistry. The main problem of insolubility in aqueous media has been solved by developing a synthetic protocol that allows highly water-soluble carbon NTs to be obtained. As a result, biologically active peptides can be easily linked through a stable covalent bond to carbon NTs. We have demonstrated that a bound peptide from the foot-and-mouth disease virus, corresponding to the 141-159 region of the viral envelope p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
294
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 506 publications
(302 citation statements)
references
References 36 publications
2
294
0
6
Order By: Relevance
“…If an antigen is linked to a CNT, the resulting construct could be more easily phagocytosed and rapidly introduced into the immune system, thus improving the antibody response. Pantarotto et al [53,54] demonstrated the potential of using CNTs for animal 90 immunization. In their seminal work, a peptide from the foot-and-mouth disease virus (FMDV) was covalently coupled to amino-derivatized single-walled carbon nanotubes (SWNTs), and this conjugate was administered to mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If an antigen is linked to a CNT, the resulting construct could be more easily phagocytosed and rapidly introduced into the immune system, thus improving the antibody response. Pantarotto et al [53,54] demonstrated the potential of using CNTs for animal 90 immunization. In their seminal work, a peptide from the foot-and-mouth disease virus (FMDV) was covalently coupled to amino-derivatized single-walled carbon nanotubes (SWNTs), and this conjugate was administered to mice.…”
Section: Introductionmentioning
confidence: 99%
“…[63] Loading values for 5 of approximately 18, 10, 10, and 7 g per milligram of CNT were calculated for 1c, 2c, 3c, and 4c, respectively. Instead of using other common procedures for protein quantification, such as TGA, [72, 365 76] the Kaiser test for amine residues, [53,77] or Bradford analysis of the unbound protein,[55] the ELISA technique was chosen to estimate the protein loading in CNTs because this method gives the amount of conjugate through the interaction with the antibody, thus confirming that the hapten is actually exposed to the environment and therefore free to interact with antibodies and cell receptors during the immune response. 370…”
mentioning
confidence: 99%
“…For instance, f -CNTs with N-protected glycine were achieved using N-protected amino acid, which were subsequently used to link biomolecules (e.g. bioactive peptides) by fragment condensation or selective chemical ligation (see Section 3.5) [148,149].…”
Section: Cycloadditionmentioning
confidence: 99%
“…Among the novel delivery options, CNTs have emerged as a promising option for biomedical applications. This is because CNTs can enter into the cells and can be functionalized (see Section 3.4) [148,190]. The later property makes them soluble, nontoxic and permits modification of their surface [7].…”
Section: Cnts As Delivery Devices For Antigens and Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation